2019
DOI: 10.1002/cssc.201802382
|View full text |Cite
|
Sign up to set email alerts
|

High‐Performance Photoelectrochemical Water Oxidation with Phosphorus‐Doped and Metal Phosphide Cocatalyst‐Modified g‐C3N4 Formation Through Gas Treatment

Abstract: Graphitic carbon nitride (g‐C3N4) has been widely explored as a photocatalyst for water splitting. The anodic water oxidation reaction (WOR) remains a major obstacle for such processes, with issues such as low surface area of g‐C3N4, poor light absorption, and low charge‐transfer efficiency. In this work, such longtime concerns have been partially addressed with band gap and surface engineering of nanostructured graphitic carbon nitride (g‐C3N4). Specifically, surface area and charge‐transfer efficiency are si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…The increased carrier density may be one of the reasons responsible for the improved photocurrent of reduced ZnO; however, in contrast to the large enhancement (3-fold) in photocurrent, the increase (no more than 2-fold) in Nd is fairly limited. In general, doubling or further enhancement of the photocurrent requires an increase of the Nd value over 1 order of magnitude, as already observed in nitrogen-annealed hematite, hydrogen-annealed TiO 2 , or phosphine-annealed g-C 3 N 4 . This result clearly indicates that there are may be some hidden factors that account for the improved performance of reduced ZnO.…”
Section: Resultssupporting
confidence: 70%
“…The increased carrier density may be one of the reasons responsible for the improved photocurrent of reduced ZnO; however, in contrast to the large enhancement (3-fold) in photocurrent, the increase (no more than 2-fold) in Nd is fairly limited. In general, doubling or further enhancement of the photocurrent requires an increase of the Nd value over 1 order of magnitude, as already observed in nitrogen-annealed hematite, hydrogen-annealed TiO 2 , or phosphine-annealed g-C 3 N 4 . This result clearly indicates that there are may be some hidden factors that account for the improved performance of reduced ZnO.…”
Section: Resultssupporting
confidence: 70%
“…The maximum rate constant value observed for CZS-25 NC indicated that the synergistic effect between SGN, Cu, and ZnO has improved the number of active sites, and correspondingly enhanced the photocatalytic efficiency against MB dye. [56][57][58] Nonetheless, as the quantity of S-g-C 3 N 4 in CZS NCs was increased beyond 25%, the photocatalytic performance of CZS NCs consistently decreased. This effect is consistent with previous ndings, which show that as the constituent content surpasses the optimum value, the photocatalytic efficacy of the type-II nanoheterostructures decreases.…”
Section: Surface Area Analysismentioning
confidence: 99%
“…Polymeric carbon nitrogen (C 3 N 4 ), a known efficient visible light responsive photocatalyst, is among the most attractive candidates due to its low cost, excellent thermal and chemical stability, and moderate band gap. [14][15][16][17][18] Nevertheless, the photocatalytic performance of pristine C 3 N 4 is still unsatisfactory due to its fairly poor active sites, limited utilization of visible light and fast recombination of charge carriers. [19][20][21] Typically, nanostructure engineering and heterojunction design are two effective methods to overcome the above drawbacks currently.…”
Section: Introductionmentioning
confidence: 99%